Not my fault - Howe, Cath (Nosy Crow, 2019)
"Maya and Rose won't talk to each other. Even though they are sisters. Not since the accident. Maya is running wild, and Rose doesn't know what to do. Now Maya and Rose have to go away together on a week-long school journey. But will the trip - and a life-threatening adventure - fix their relationship... or break it for good? A beautiful story of family, forgiveness, and finding out who you are, from the author of the highly-acclaimed Ella on the Outside. Praise for Ella on the Outside: A perfectly-pitched, thoughtful story with a big heart. - Katherine Woodfine, author of The Clockwork Sparrow It's impossible not to root for Ella to be brave and make the right decisions, and the urge to find out whether she will powers this warm, considered and entertaining novel"--BookTrust